Physiological criteria of functional fitness and determinants of physical work capacity of highly skilled wrestlers - Pryimakov, O.; Iermakov, S.; Eider, J.; Prysiazhniuk, S.; Mazurok, N. (Physical Education of Students, 2020)
The objective of the work is to study the key factors of highly skilled wrestler fitness structure determining the level of their functional state and physical work capacity at the stage of maximum realization of individual capacities.Material: 45 highly skilled wrestlers aged 19-27 years, members of the national teams of Ukraine in freestyle and Greco-Roman wrestling were examined. The 27 of Ukrainian National Team athletes, participated in this study, were at the student`s age (19-24 y) during championships and 23 of them were currently students. Instrumental research methods were used to record indices of functional fitness (FF) and physical work capacity of wrestlers while performing a specialized test with throws of a partner and a block of testing physical loads on a bicycle ergometer. Results: It was revealed that among factors determining the structure of wrestlers` fitness, the integral factor of FF general level (31.13% of the total variance) has the greatest impact on the variability of physical work capacity indices of athletes. Increase in skill level of wrestlers is associated with decreased time of performing throws in a specialized test, increased relative values of lactate power, O2-debt, general level of FF, O2 consumption per 1 kg of body mass. Improvement of wrestler FF structure along with an increase in their skill level is characterized by higher contribution of FF integral parameters (anaerobic power, mobility of physiological reactions, FF general level) to the manifestation of physical work capacity. It was revealed that the general level of FF of wrestlers is characterized by the following ratio of key factors (relative to model values of elite athletes): anaerobic power - 52.6 ± 4.9%, aerobic power - 52.8 ± 4,1%, mobility - 80.4 ± 5.3%, economy - 43.3 ± 3.0%. In the course of studies, mathematical models of the key factors of wrestler FF structure associations with the level of special work capacity, skill level and weight category have been developed. Modeling allowed to specify the criteria and develop scales for assessing special physical work capacity level, differentiated according to skill level and weight category groups of highly skilled wrestlers.Conclusions: The findings reflect the crucial role of anaerobic energy supply mechanisms in the manifestation of high special work capacity in wrestling. Improvement of wrestler FF structure along with the increase of their skills is characterized by a decrease in the number of key functional parameters determining the level of physical work capacity during testing with loads that model specific activity of highly skilled wrestlers. This, along with body functions economization, is one of the important criteria for improving FF structure of the combat athletes.